Fertility Preservation for Cancer Patients: A Review. (31st March 2010) - Ajala, Tosin; Rafi, Junaid; Larsen-Disney, Peter; Howell, Richard
Abstract : Infertility can arise as a consequence of treatment of oncological conditions. The parallel and continued improvement in both the management of oncology and fertility cases in recent times has brought to the fore-front the potential for fertility preservation in patients being treated for cancer. Oncologists must be aware of situations where their treatment will affect fertility in patients who are being treated for cancer and they must also be aware of the pathways available for procedures such as cryopreservation of gametes and/or embryos. Improved cancer care associated with increased cure rates and long term survival, coupled with advances in fertility treatment means that it is now imperative that fertility preservation is considered as part of the care offered to these patients. This can only be approached within a multidisciplinary setting. There are obvious challenges that still remain to be resolved, especially in the area of fertility preservation in prepubertal patients. These include ethical issues, such as valid consent and research in the area of tissue retrieval, cryopreservation, and transplantation.